Fecundity and egg diameter of blue swimming crab (Portunus pelagicus) in Kawal Waters, Riau Islands Province-Indonesia - Wiradinata, Hardi; Susiana, Susiana; Muzammil, Wahyu (Agrikan: Jurnal Agribisnis Perikanan, 2021)
Blue swimming crab (Portunus pelagicus), an important global fishery resource, because it widely used by various countries because it has a high export value. The purpose of this study was to determine the fecundity and egg diameter of blue swimming crab in Kawal waters, Bintan Regency, Riau Islands Province, Indonesia. The method used in this study a survey method. The sampling technique was carried out by sensus sampling with a total sample of 176 ind. Fecundity obtained during the study varied from the smallest to the largest. Sampling The least fecundity was found in the fourth sampling female blue swimming crab and the highest fecundity was found in the third sampling female blue swimming crab. The average number of blue swimming crab fecundity obtained in this study amounted to 1,177,941 eggs. The egg diameter of blue swimming crab obtained during the study had different values during the study. Where the first sampling has an average value of 441.47 µm, the second sampling has an average value of 370.63 µm, then the third sampling has an average value of 421.44 µm, and the last fourth sampling has an average value of 375.04 µm.